Introduction to the lectures on the history of philosophy - Hegel, Georg Wilhelm Friedrich (Clarendon press, 1985)
Contents: I. Introduction to the lectures on the history of philosophy; II. Berlin introduction (1820); III. Introduction of 1823, 1825, and 1827.